Sensitivity analysis of geometric errors in additive manufacturing medical models. Issue 3 (March 2015) - Pinto, Jose Miguel; Arrieta, Cristobal; Andia, Marcelo E.; Uribe, Sergio; Ramos-Grez, Jorge; Vargas, Alex; Irarrazaval, Pablo; Tejos, Cristian
Highlights In additive manufacturing each building step introduces errors to the models. Models errors are concentrated at regions with high curvatures. Triangulation resolution and segmentation threshold are critical error factors. Errors could be reduced choosing better triangulation and printing resolutions. More robust segmentation algorithms should be considered for the building process.